Phase I/II trial of bendamustine, ixazomib, and dexamethasone in relapsed/refractory multiple myeloma - Dhakal, Binod (Blood Cancer J, 2019)
In this phase I/II trial, BID, bendamustine (70, 80, or 90 mg/m(2)), ixazomib (4 mg), and dexamethasone (40 mg), was administered to 28 patients with relapsed and/or refractory multiple myeloma (RRMM) exposed to bortezomib and lenalidomide and refractory to at least one. A 3 + 3 dose escalation based on dose-limiting toxicities (DLTs) was employed in phase I (total 15); 2/6 patients developed DLTs (neutropenia and thrombocytopenia) at dose level 3 establishing the recommended phase II dose as bendamustine 80 mg/m(2), ixazomib 4 mg, and dexamethasone 40 mg. The median age was 67 years (range, 42–72), and 43% were females. Patients received a median of 4 (range, 4–9) prior lines of therapy, of which ~50% were double refractory. In phase II, total 19 patients were treated. With a median follow-up of 17 months, 11% achieved very good partial response, 50% achieved partial response, and 27% achieved stable disease. Median progression free (PFS) and overall (OS) survival were 5.2 months (95% CI, 1.96–8.3) and 23.2 months (95% CI 16.3–30.07). The most frequent adverse events were anemia, thrombocytopenia, leukopenia, nausea, diarrhea, and infections. Peripheral neuropathy was infrequent. BID is a well-tolerated and effective combination therapy for patients with RRMM.